HUBUNGAN SANITASI RUMAH TERHADAP KEJADIAN PENYAKIT KULIT DERMATITIS DI WILAYAH KERJA PUSKESMAS PALANGKAU KECAMATAN KAPUAS MURUNG - Saputri, Maulita; Santoso , Imam; Syarifudin A, Syarifudin A (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Dermatitis is a skin disorder with subjective symptoms in the form of itching and objectively characterized by spots, rashes or inflammation. In the data recorded from the UPT Puskesmas Palangkau from 2021, 2022 and 2023 (January to November) there were 270 cases of dermatitis skin disease. This research was conducted with the aim of finding out the relationship between home sanitation, which consists of the availability of clean water, waste management, waste water management and family toilet facilities, with the incidence of dermatitis in the community.This type of research is analytical observation, the research design uses case control. The sample consisted of 26 cases and 52 controls. The instrument used in this research was an observation sheet. Data analysis used Somers’d statistical test. Somers’d statistical test results show that there is a significant relationship between the availability of clean water and the incidence of dermatitis skin disease (p = 0.000 < α = 0.05 OR = 28.576) and there is a significant relationship between waste management and the incidence of dermatitis skin disease (p = 0.000 < α = 0.05 OR = 0).